Consider the function f : R − { 0 , 1 2 } → R such that
f ( x ) + f ( 1 − x 1 2 ) = x .
Which of the following statements is true?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
Wrong Ones:
Let x = − 1 6 8 1 .
Plugging into the equation, we get f ( − 1 6 8 1 ) + f ( 2 0 1 7 ) = − 1 6 8 1 ⇔ f ( 2 0 1 7 ) = − 1 6 8 1 − f ( − 1 6 8 1 ) , not f ( 2 0 1 7 ) = 1 6 8 1 + f ( 1 6 8 1 ) . ■
By taking the implicit derivative of f ( x ) + f ( 1 − x 1 2 ) = x , we find that f ′ ( x ) + f ′ ( 1 − x 1 2 ) ⋅ x 2 1 2 = 1 .
Letting x = 1 2 we see that f ′ ( 1 2 ) + f ′ ( 1 − 1 2 ) = 1 , and not f ′ ( 1 2 ) + f ′ ( − 1 2 ) = 1 . ■
Let x = 1 − x 1 2 .
Plugging into the equation, it yields us f ( 1 − x 1 2 ) + f ( 1 − 1 − x 1 2 1 2 ) = 1 − x 1 2 .
Subtracting this equation from the original one, we get f ( x ) − f ( 1 − 1 − x 1 2 1 2 ) = x − 1 + x 1 2 .
But x − 1 + x 1 2 can never be equal zero, so we will never have f ( x ) = f ( 1 − 1 − x 1 2 1 2 ) . ■
Right One:
Let x = 3 .
Plugging into the equation, we get f ( 3 ) + f ( − 3 ) = 3 .
If the function were odd, we would have gotten f ( 3 ) + f ( − 3 ) = 0 .
Thus, the function can't be odd.